An Extension of Taylor's φ-Circle Method and Some Stability Charts for Submerged Slopes. (28th August 2020) - Li, Ping; Dong, Luanhua; Gao, Xiaowen; Li, Tonglu; Hou, Xiaokun
Abstract : Taylor's φ -circle method is a classical method for slope stability calculation, which has analytical solutions. Taylor derived equations in two cases separately, namely, (i) the outlet of the critical failure surface is at the slope toe and (ii) the outlet of the failure surfaces is not at the slope toe. The method is only appropriate for two conditions (without underground water table in slopes or totally submerged slopes). In this study, a general equation that unifies the equations of the two cases is proposed and partially submerged condition is introduced. The critical failure surfaces corresponding to the minimum factor of safety are determined using the computer program proposed by the authors. The general expression of the safety factor of slopes under the following four conditions is derived, namely, (i) partly submerged, (ii) completely submerged, (iii) water sudden drawdown, and (iv) water slow drawdown. The corresponding charts for practical use are available.